2005
DOI: 10.1002/marc.200500590
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Polypyrrole and Poly(allylamine hydrochloride) Nanotubes Fabricated with Layer‐by‐Layer Assembly

Abstract: Summary: Conductive nanotubes were fabricated by the alternate adsorption of negatively charged polypyrrole (PPy) and positively charged poly(allylamine hydrochloride) (PAH) onto the inner pores of polycarbonate templates. Nanotubes are obtained by the subsequently removal of the template. Using several microscopic and spectroscopic techniques, we demonstrate that the yielded materials possess a tubular structure and conductive properties. The conductivity of PPy/PAH nanotubes is measured as 0.008 S · cm−1.SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 44 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…For example, Ai et al prepared polypyrrole/poly(allylamine hydrochloride) nanotubes consisting of six or 12 bilayers in PC membranes with a D p -value of 400 nm that had initially been coated with poly(ethylenimine) [238]. Again, the observed value of the wall thickness of the nanotubes of some tens of nanometers was much larger than that of corresponding multilayer systems deposited on smooth substrates.…”
Section: Multilayer Nanotubes By Layer-by-layer Depositionmentioning
confidence: 90%
“…For example, Ai et al prepared polypyrrole/poly(allylamine hydrochloride) nanotubes consisting of six or 12 bilayers in PC membranes with a D p -value of 400 nm that had initially been coated with poly(ethylenimine) [238]. Again, the observed value of the wall thickness of the nanotubes of some tens of nanometers was much larger than that of corresponding multilayer systems deposited on smooth substrates.…”
Section: Multilayer Nanotubes By Layer-by-layer Depositionmentioning
confidence: 90%
“…Our previous studies have demonstrated that the wall thickness of the assembled nanotubes with the LbL assembly depends in some sense on the number of assembly layer [11,[28][29][30]. In view of this, we performed the following two experiments by choosing different assembly circles.…”
Section: Controlling the Wall Thickness Of Nanotubesmentioning
confidence: 99%
“…[16][17][18] In most cases, the sizes, shapes, and other structural properties of the assembled system can be well controlled by the pore structure obtained by using the template method. [19,20] Herein, we use the template technique combined with the LbL assembly method to fabricate complex nanotubes through hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%